2006
DOI: 10.1507/endocrj.k06-015
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Severity of Hashimoto's Disease and the Functional +874A/T Polymorphism in the Interferon-.GAMMA. Gene

Abstract: Abstract. CD8 + CD25 + -activated cytotoxic T cells and anti-thyroglobulin antibodies (TgAb) are independently involved in the severity of Hashimoto's disease (HD). Interferon γ (IFN-γ) activates cytotoxic T cells. To evaluate the hypothesis that the functional +874A/T polymorphism in the gene encoding IFN-γ is associated with the severity of HD, we examined the frequencies of this polymorphism in 34 HD patients who developed hypothyroidism (severe HD); 22 untreated, euthyroid HD patients (mild HD); 49 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…We previously reported that a high genetic expression of IFN-γ and a high proportion of Th1 cells were associated with the severity of HD [8,10]. IL-18 enhanced the production of Th1 cytokines, such as IFN-γ [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that a high genetic expression of IFN-γ and a high proportion of Th1 cells were associated with the severity of HD [8,10]. IL-18 enhanced the production of Th1 cytokines, such as IFN-γ [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Th1 cells mainly produce interferon (IFN)-γ that promotes cell-mediated immunity [1,3,4]. We previously reported that CD8 + CD25 + activated cytotoxic T cells and Th1 cells were increased in patients with severe HD [8,9] and that higher production of IFN-γ was more frequent in patients with severe HD than in those with mild HD [10]. Moreover, lower expression of T-box 21 (TBX21), the master transcription factor of Th1 cells, was associated with intractability of GD [11].…”
mentioning
confidence: 99%
“…IFN-γ, TNF-α) were shown to play a crucial role in the pathogenesis and severity of autoimmune thyroid diseases [7][8][9][10]. However, the trigger of the induction has not been well understood.…”
Section: Methods and Definitionsmentioning
confidence: 99%
“…Likewise, the intractability of Graves disease (GD) is difficult to predict. Autoimmune thyroid destruction that underlies both diseases is strongly determined by T-cell cytotoxicity, which is activated by interferon (IFN)-␥ (1 ), and the T allele in ϩ874A/T polymorphism of the interferon gamma (IFNG) gene, which promotes increased IFN-␥ production, has been noted more frequently among patients with severe HD (2 ). Cytokine balance between T-helper 1 (Th1) cytokines, such as IFN-␥, and Th2 cytokines is important in immune regulation (3 ).…”
Section: To the Editormentioning
confidence: 99%